Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

1÷(secA-tan A)=secA+tanA how to prove,....,.....................

1÷(secA-tan A)=secA+tanA how to prove,....,.....................

Grade:11

1 Answers

Arun
25763 Points
4 years ago
we know by identity
sec^2 A –tan^2 A= 1
(secA+tanA) (secA –tanA) = 1    by formula of a2 –b2= (a+b)(a –b)
hence secA+ tanA= 1/(secA –tanA)
hence proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free